Produção de H2 na radiólise da água - Ferreira, Natalia (2008)
The purpose of this work is to investigate the production mechanism of H2, the molecular hydrogen, in the radiolysis of liquid water by proton impact. A review of the available literature about water radiolysis shows some open questions as well as a scarce amount of experimental data. We developed a new apparatus which is used as a target for liquid water irradiation as well as a recipient to hold the gaseous products of the radiolysis. We show, in detail, how this apparatus was build up and characterized, the methodology used during the irradiation and for the measurements of the gaseous products obtained. The set of the experimental results obtained in this work was analyzed and clearly shows a large production of H2 in the experiment.